1999
DOI: 10.1074/jbc.274.50.35653
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Functional Anatomy of BgK on Kv1.1, Kv1.2, and Kv1.3

Abstract: BgK is a peptide from the sea anemone Bunodosoma granulifera, which blocks Kv1.1, Kv1.2, and Kv1.3 potassium channels. Using 25 analogs substituted at a single position by an alanine residue, we performed the complete mapping of the BgK binding sites for the three Kv1 channels. These binding sites included three common residues (Ser-23, Lys-25, and Tyr-26) and a variable set of additional residues depending on the particular channel. Shortening the side chain of Lys-25 by taking out the four methylene groups d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 47 publications
5
63
0
Order By: Relevance
“…Three residues (S20, K22, and Y23 in ShK; S23, K25 and Y26 in BgK) are strictly conserved in all SAK-I toxin sequences, and represent a common core of hot spot residues for pharmacological activity ( Fig. 2a) (Alessandri-Haber et al 1999;Castaneda et al 1995;Gasparini et al 2004;Gendeh et al 1997b;Minagawa et al 1998;Pennington et al 1996a, b;Schweitz et al 1995). Alanine mutation analyses have shown that other residues (I7, R11, H19, R24 and F27 in ShK), which are clustered around the three conserved residues, are also important for the binding activity of ShK to Kv1.2 channels in brain membranes, and to Kv1.3 channels in T lymphocytes (Pennington et al 1996a, b;Rauer et al 1999).…”
Section: Sea Anemone Toxins Interacting With Kv1 Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three residues (S20, K22, and Y23 in ShK; S23, K25 and Y26 in BgK) are strictly conserved in all SAK-I toxin sequences, and represent a common core of hot spot residues for pharmacological activity ( Fig. 2a) (Alessandri-Haber et al 1999;Castaneda et al 1995;Gasparini et al 2004;Gendeh et al 1997b;Minagawa et al 1998;Pennington et al 1996a, b;Schweitz et al 1995). Alanine mutation analyses have shown that other residues (I7, R11, H19, R24 and F27 in ShK), which are clustered around the three conserved residues, are also important for the binding activity of ShK to Kv1.2 channels in brain membranes, and to Kv1.3 channels in T lymphocytes (Pennington et al 1996a, b;Rauer et al 1999).…”
Section: Sea Anemone Toxins Interacting With Kv1 Channelsmentioning
confidence: 99%
“…This is why, to allow a more extensive use of these very useful pharmacological tools, especially for in vivo studies which use large amounts of material, a number of the sea anemone K + channel inhibitors like ShK or BgK, have been chemically synthesized. Solid-phase synthesis allows the obtaining of "mg" of linear peptides which then require to be folded to their biologically active forms (Alessandri-Haber et al 1999;Cotton et al 1997;Pennington et al 1995). The synthetic peptides display the same activity on K + channels as the native toxins.…”
Section: Purification and Synthesis Of Sea Anemone K Channel Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last is the ion channel regulatory (ICR) domain at the C-terminal (magenta), named for its ability to block or modulate a variety of voltage-dependent potassium and calcium channels as well as ryanodine receptors (Gibbs et al 2006 ). The ICR domain is similar in tertiary structure to ion channelblocking peptides from sea anenomes (Pennington et al 1999 ;Alessandri-Haber et al 1999 ;Cotton et al 1997 ).…”
Section: Introductionmentioning
confidence: 99%